Bond mechanism and bond strength of GFRP bars to concrete: A review - Yan, Fei; Lin, Zhibin; Yang, Mijia (Composites. Part B, Engineering, 2016)
Glass fiber-reinforced polymer (GFRP) reinforcements are taken as an alternative solution for the deterioration of civil infrastructures. GFRP bars have received increasing attention due to low cost compared to carbon fiber-reinforced polymer (CFRP) bars. Bond characteristic of GFRP bars in concrete is the most critical parameter for implementation of the material to the corrosion-free concrete structures. Unlike steel reinforcement, GFRP materials behave anisotropic, non-homogeneous and linear elastic properties, which may result in different force transfer mechanism between reinforcement and concrete. With the purpose of covering the most valuable contributions regarding bond mechanism in the past work, a comprehensive review focusing on the failure mode and bond strength is carried out in this paper. A database consisted of 682 pullout-test specimens was created to observe the factors affecting bond behavior. Basic relationship between bond strength/slip and factors was analyzed accordingly. In addition, the development of bond degradation under environmental conditions, such as freezing-thawing cycling, wet-dry cycling, alkaline solutions and high temperature was presented thereafter. These environmental influences need to be further investigated.